2013
DOI: 10.1007/s00216-013-7108-6
|View full text |Cite
|
Sign up to set email alerts
|

Innovative detection methods for aquatic algal toxins and their presence in the food chain

Abstract: Detection of aquatic algal toxins has become critical for the protection of human health. During the last 5 years, techniques such as optical, electrochemical, and piezoelectric biosensors or fluorescent-microsphere-based assays have been developed for the detection of aquatic algal toxins, in addition to optimization of existing techniques, to achieve higher sensitivities, specificity, and speed or multidetection. New toxins have also been incorporated in the array of analytical and biological methods. The im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 128 publications
0
22
0
Order By: Relevance
“…Algal toxins, phycotoxins, and cyanotoxins, in turn, are produced by toxicogenic microalgae and cyanobacteria, and they can enter the marine food chain via phytoplankton and subsequently to humans by contaminated seafood. Several small molecule toxins originating from seafood are known to cause severe illnesses, such as paralytic shellfish poisoning, puffer fish poisoning, and neurotoxic shellfish poisoning, and it has been reported that seafood poisonings are increasing in frequency and new intoxications are emerging [5,6]. All the aforementioned toxins are known to cause, besides a threat to human and animal health, but also substantial economic losses in aqua- and agriculture, and many of them fall under national and international regulations.…”
Section: Origin and Occurrence Of Small Moleculesmentioning
confidence: 99%
“…Algal toxins, phycotoxins, and cyanotoxins, in turn, are produced by toxicogenic microalgae and cyanobacteria, and they can enter the marine food chain via phytoplankton and subsequently to humans by contaminated seafood. Several small molecule toxins originating from seafood are known to cause severe illnesses, such as paralytic shellfish poisoning, puffer fish poisoning, and neurotoxic shellfish poisoning, and it has been reported that seafood poisonings are increasing in frequency and new intoxications are emerging [5,6]. All the aforementioned toxins are known to cause, besides a threat to human and animal health, but also substantial economic losses in aqua- and agriculture, and many of them fall under national and international regulations.…”
Section: Origin and Occurrence Of Small Moleculesmentioning
confidence: 99%
“…This technique is compatible with simple extraction protocols for marine biotoxins and is sensitive enough to detect these toxins below the regulated limit in shellfish samples as well as in algae and seawater. The high degree of automation, the potential to create portable devices and the ease-of-use make SPR-based immunosensors a potential tool for toxin detection [100,101]. Feltis et al [102] developed the first hand-held and field-deployable SPR biosensor for detection of security sensitive proteotoxins.…”
Section: Label-free Technologiesmentioning
confidence: 99%
“…Traditionally, these toxins have been detected in seafood using laborious biological and animal reference methods. The release of the European Union Directive 86/609 for animal protection to ensure progress away from animal experimentation to scientifically acceptable validated non-animal procedures started the scientific exploration for alternative methods for these animal bioassays [90,91]. Biosensor technologies are analytical tools for the recognition and measurement of a target through its association with a biological component and physiochemical detector.…”
Section: Biosensorsmentioning
confidence: 99%